1996
DOI: 10.1152/ajprenal.1996.271.3.f489
|View full text |Cite
|
Sign up to set email alerts
|

Urodilatin is involved in sodium homeostasis and exerts sodium-state-dependent natriuretic and diuretic effects

Abstract: Urodilatin is involved in sodium homeostasis exerts sodium-state-dependent natriuretic and diuretic cts. Eight male volunteers participated in a study consisting of three consecutive phases of 7 days each. The volunteers a sodium diet with 52, 172.6, and 347.8 mmol um/day. Sodium excretion increased from 57.4 +/- 3.7 via .8 +/- 4.6 (P < 0.001) to 322.5 +/- 10.2 mmol/24 h (P < 0.001) at the end of each sodium diet. Urinary urodilatin excretion increased from 24.8 +/- 3.0 via 35.5 +/- 9.0 (P = 0.07) to 49.0 = mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 0 publications
0
24
3
Order By: Relevance
“…Urodilatin is exclusively found in urine and in the kidney suggesting that it participates in the intrarenal regulation of sodium homoeostasis in a paracrine manner, but its physiological function is still incompletely understood [10,11]. Since urodilatin appears to contribute to the sodium excretion during hypervolaemic states [12], we hypothesized that the radiocontrast-induced diuresis may be associated with an increased urodilatin excretion. Therefore we measured the fractional excretion of sodium and urodilatin in the urine, as well as the plasma concentrations of atrial natriuretic peptide and creatinine in patients before and after coronary angiographic procedures to test the hypotheses that a) the diuresis following intravascular radiocontrast administration is a natriuresis which b) correlates with the urinary excretion of urodilatin.…”
Section: Introductionmentioning
confidence: 99%
“…Urodilatin is exclusively found in urine and in the kidney suggesting that it participates in the intrarenal regulation of sodium homoeostasis in a paracrine manner, but its physiological function is still incompletely understood [10,11]. Since urodilatin appears to contribute to the sodium excretion during hypervolaemic states [12], we hypothesized that the radiocontrast-induced diuresis may be associated with an increased urodilatin excretion. Therefore we measured the fractional excretion of sodium and urodilatin in the urine, as well as the plasma concentrations of atrial natriuretic peptide and creatinine in patients before and after coronary angiographic procedures to test the hypotheses that a) the diuresis following intravascular radiocontrast administration is a natriuresis which b) correlates with the urinary excretion of urodilatin.…”
Section: Introductionmentioning
confidence: 99%
“…And indeed, baseline urinary NTproBNP was higher in the present study than in the previous one [1] , while volume loading did not induce a further increase in this parameter. In contrast to this, Meyer et al [14] have shown a more pronounced increase in the excretion of the renal natriuretic peptide urodilatin following intravenous sodium loading during a sodium-enriched diet in comparison with a low-sodium state. This discrepancy cannot be solved by the present data.…”
Section: Discussionmentioning
confidence: 87%
“…So far, most studies dealing with the mechanisms regulating excretion and production of the natriuretic peptide urodilatin have focussed on the effects of different sodium loads [1], variations in central thoracic blood volume [4] and renal perfusion pressure [2] on U URO V. However, it is unclear which, if any, humoral factors mediate these effects at the level of the kidney. Since the renin-angiotensin system is also involved in the regulation of sodium and water homeostasis and renal perfusion pressure [5], this hormonal system likely interferes with U URO V.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms regulating the production and excretion of the kidney-derived peptide urodilatin (ANP-95-126), which is presumed to act as a paracrine hormone in the regulation of sodium and water homeostasis, remain to be illucidated [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation